Globalising the local in children's television for the post-network era: How Disney+ and BBC Studios helped Bluey the Australian cattle dog jump the national fence. (March 2021) - Potter, Anna
Online television services are changing the way television is funded, produced and experienced by its national and global audiences, with profound cultural implications. The case study presented here of Australian production company Ludo Studio and the animated series Bluey provides valuable insights into the increasingly complex interactions between the local and the global in television production, and the cultural counterflows they can engender. Television made for online distribution can encompass national policy settlements, funding bodies and public service media as well as globally oriented distribution arrangements on SVODs such as Disney +, Netflix and Amazon Prime Video. Drawing on interview material with Bluey's key creatives, this research identifies how globalising influences are both shaping and amplifying the local in children's television production cultures.